FINANCIAL EDUCATION TOWARDS EARLY INVESTMENT IN HIGH SCHOOL STUDENTS: EVIDENCE FROM A RADOMIZED EXPERIMENT - Nugroho, Vina; Budhidharma, Valentino; Kim, Sung Suk (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This study investigate the effect of financial literacy towards investment decision among high school students in Jabodetabek. Students were provided with workshop of financial investment. This study address the following questions : are young people are financially literate? How can we enhance their financial literacy? We did pre test and post test for them. From pre test analysis, we found that most young peoples are not familiar with financial literacy. Because, only 39% from sample are familiar with concept of inflation. We use “interest rate” and “inflation” questions to be tested whether respondents were knowledgeable about those two criteria. This paper uses randomized experience to explore how financial literacy changes investment decision among young peoples. The effect of financial literacy program are strong. After having workshop, students are more knowledgeable about financial literacy that might be useful for their financial decision.